PENGARUH DUKUNGAN KELUARGA TERHADAP TINGKAT DEPRESI PADA LANJUT USIA DI DAERAH ISTIMEWA YOGYAKARTA: The Influence of Family Support on Depression Levels of Elderly in Yogyakarta - Aini Inayati; Dwiky Imam Ichsani (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2019)
Background: The elderly is the final stage of the human life cycle, today the depression in elderly is an interaction of biological, psychological and social factors. Social factors are decreasing social interaction, loneliness, mourning and poverty can trigger depression. Objective: To determine the effect of family support on the level of depression in elderly in Yogyakarta Method: This study used quantitative research design with cross sectional approach. The sample used was 97 elderly who met the criteria for inclusion and exclusion. Sampling in this study used purposive sampling with data analysis using SPSS 17.0. Results: The results of the Spearman Rank test obtained a significance value (2-tailed) with a result of 0.001 which means 0.001 <0.05, then H1 is accepted meaning that there is a significant relationship between family support with the level of depression in elderly in Nganglik, Sleman, Yogyakarta. While the level of depression in elderly found mild depression 18.6% (18 responses), moderate depression as much as 78.4% (76 respondents) and major depression as much as 3.1% (3 respondents). Conclusion: Family support is very beneficial in controlling depression of the elderly and also reduce the pressures that exist in conflicts that occur in the elderly. Family support is related to the formation of mental balance and psychological satisfaction. Support is obtained from families consisting of husband or wife, children, grandchildren, siblings, or close relatives of the elderly.